Joint Inversion of Receiver Functions and Apparent Incidence Angles to Determine the Crustal Structure of Mars. Issue 3 (7th February 2023) - Joshi, Rakshit; Knapmeyer‐Endrun, Brigitte; Mosegaard, Klaus; Wieczorek, M. A.; Igel, Heiner; Christensen, Ulrich R.; Lognonné, Philippe
Abstract: Recent estimates of the crustal thickness of Mars show a bimodal result of either ∼20 or ∼40 km beneath the InSight lander. We propose an approach based on random matrix theory applied to receiver functions (RFs) to further constrain the subsurface structure. Assuming a spiked covariance model for our data, we first use the phase transition properties of the singular value spectrum of random matrices to detect coherent arrivals in the waveforms. Examples from terrestrial data show how the method works in different scenarios. We identify three previously undetected converted arrivals in the InSight data, including the first multiple from a deeper third interface. We then use this information to jointly invert RFs with the absolute S‐wave velocity information in the polarization of body waves. Results show a crustal thickness of 43 ± 5 km beneath the lander with two mid‐crustal interfaces at depths of 8 ± 1 and 21 ± 3 km. Plain Language Summary: Recent analysis of seismic data from InSight shows that the crustal thickness beneath the InSight lander can be either 20  or 40 km. To resolve this ambiguity, we apply results from random matrix theory to receiver function (RF) analysis. The distribution of singular values of a random matrix shows well‐behaved deterministic properties that can be used to separate them from those of an underlying coherent signal if present. We use examples from terrestrial data to show how the method works. When applied to RFs computed from InSight seismic data, we identify three new energy arrivals, including one that supports the existence of a deeper third layer. Using this information, we simultaneously inverted the RF data along with the measured incidence angle of body waves. Results show a crustal thickness of 43 ± 5 km beneath the lander with two mid‐crustal interfaces at depths of 8 ± 1 and 21 ± 3 km. Key Points: We apply recent results from random matrix theory to identify crustal phases in noisy receiver functions for Mars from InSight data Once identified, we jointly invert these phases with frequency‐dependent apparent S‐wave velocity curves Results show a crustal thickness of 43 km with two inter‐crustal discontinuities at 8 and 21 km beneath the lander